Patient Portals: Useful for Whom and for What? A Cross-Sectional Analysis of National Survey Data - Swoboda, Christine M.; DePuccio, Matthew J.; Fareed, Naleef; McAlearney, Ann Scheck; Walker, Daniel M. (Applied Clinical Informatics, 2021)
Background Patients who use patient portals may be more engaged and empowered in their care; however, differences in who accesses patient portals remain. The characteristics of who uses patient portals more frequently and who perceives them as useful may also differ, as well as which functions people use.Objective We assessed the characteristics of patient portal users to examine who uses them more frequently and who perceives them as useful. In addition, we wanted to see if those who use them more frequently or perceive them to be more useful use different functions or more functions of patient portals.Methods Pooled cross-sectional data from 2017 to 2018 Health Information National Trends Survey (HINTS) were used. Ordinal regression models were developed to assess frequency of use and perceived usefulness by demographics, and multivariable logistic regression models were used to examine the association between the use of 10 patient portal functions and frequency of use and perceived usefulness of patient portals.Results The odds of using patient portals more frequently were higher among those with Bachelor's degrees, incomes between $35,000 and $75,000, and those with two or more chronic conditions. Respondents with three or more chronic conditions had higher odds of rating patient portals as useful. Those who used their patient portal 10 or more times in the past year had higher odds of using all functions except for viewing test results compared with those who used their patient portal one to two times per year. Those who rated patient portals as “very useful” had higher odds of using seven of the functions compared with those who rated them “not very”/“not at all useful.”Conclusion It is important to continue to assess usefulness, frequency of use, and overall patient portal function use to identify opportunities to increase patient engagement with patient portals.
Keywords: patient portals; electronic health record; surveys and questionnaires; public health surveillance